Leveraging GASING pedagogy and AI adoption to enhance problem-solving skills: The mediating roles of learning motivation and mathematical creativity - Umam, Khoerul; Susandi, Ardi Dwi; Surya, Yohanes (Universitas Islam Raden Intan Lampung, INDONESIA, 2026)
Purpose: The rapid integration of Artificial Intelligence (AI) into mathematics education risks fostering